ENDOMETRIOSIS: DIAGNOSTIC CHALLENGES AND ADVANCES IN TREATMENT OPTIONS - Kamoljonova Go‘zaloy Odiljon qizi (Web of Journals Publishing, 2025)
Endometriosis is a common gynaecological condition affecting a significant proportion of reproductive-age individuals. Despite its prevalence, diagnostic delays remain widespread. This article discusses the key diagnostic challenges and highlights current advances in medical and surgical management of the disease.
Keywords: Endometriosis; Diagnosis; Laparoscopy; Biomarkers; Hormonal therapy; Chronic pelvic pain; Infertility.